Polymers for bone reconstruction - evaluation of chosen polimeric substrates in osteoblasts in vitro culture - Fabianowski, W.; Polak, B.; Lewandowska-Szumieł, M. (Polimery, 2022)
In a literature review the theoretical fundamentals and achievements in osseous implants’ investigations have been presented. Especially polymeric materials used in implants were discussed as well as the criteria of the proper polymers choice. These criteria cover the structure of a polymer, porosity, mechanical and surface properties and biodegradation process course. Modification of osseous implant surface with proteins has been also discussed. The part concerning the own research contains the results of evaluation of bone cells’ (osteoblasts) adhesion to various types of biomaterials, used as porous osseous implants. A new way of evaluation, presented in Scheme A, was used. Contact angle values (CA, Fig. 1) of the surfaces obtained were measured. Also viability of cells after one-week incubation was investigated basing on the measurements of activity of enzymes of succinate dehydrogenase (XTT Test, Fig. 2) or alkaline phosphatase (ALP Test, Fig. 3). 11 series of measurements differing in the substrate type were done. The best results have been obtained for the surfaces with dextran as well as with the systems: dextran + poly(acrylic acid) (PAA), dextran + Ca(NO3)2 or dextran + PAA + Ca(NO3)2. We did not find an unambiguous correlation between biological tests results and hydrophylic or hydrophobic character of polymeric substrate.